2016
DOI: 10.1111/ors.12216
|View full text |Cite
|
Sign up to set email alerts
|

The coronectomy technique for lower third molars: past and present

Abstract: Aim: To discuss the past and present evidence for the coronectomy technique for third molars. Materials and Methods: A review of the past and present literature related to the healing of extraction sockets in the presence of root fragments. Results: High-quality research studies surrounding the coronectomy procedure are lacking and it is important therefore that surgeons are aware that change of practice is not yet supported. The long-term consequences, in terms of infection or other, are not known as study fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Our plan is to present migration of the teeth outcomes in studies of coronectomy in later papers. The cases of young people included in this study were included as their CBCT demonstrated that they were in the high‐risk group for transection of the IAN if the teeth were extracted.…”
Section: Discussionmentioning
confidence: 99%
“…Our plan is to present migration of the teeth outcomes in studies of coronectomy in later papers. The cases of young people included in this study were included as their CBCT demonstrated that they were in the high‐risk group for transection of the IAN if the teeth were extracted.…”
Section: Discussionmentioning
confidence: 99%
“…Data were extracted from the online Web of Science (WoS) database hosted by Clarivate Analytics. With reference to previously‐published narrative and systematic reviews on coronectomy, the search strategy was defined to be: Topic = (coronectom* OR partial odontectom*). The search included papers with the words “coronectomy” and “partial odontectomy”, and their variants in the title, abstract, or keywords.…”
Section: Methodsmentioning
confidence: 99%